A statistical protocol to describe differences among nutrient utilization patterns of Fusarium spp. and Trichoderma gamsii. (13th March 2021) - Lasinio, Giovanna Jona; Pollice, Alessio; Pappalettere, Livia; Vannacci, Giovanni; Sarrocco, Sabrina
Abstract: The Biolog phenotype microarrays (PM) system offers a simple and cheap tool to rapidly provide a high throughput of information about the phenotypes of fungal isolates in a short time. In order to improve the use of the PM system in fungal ecology studies, the present work proposes a new statistical protocol based on two approaches, that is, a functional principal components analysis to describe similarity patterns of growth curves, and a Bayesian generalized additive model (GAM) to allow inferences on specific growth features, in order to analyse nutrient fungal utilization in a model system including four causal agents of Fusarium head blight, the natural competitor Fusarium oxysporum, and the beneficial isolate Trichoderma gamsii T6085. Analysis of data collected by the Biolog PM in our biological system showed a different nutritional competitive potential of the four pathogens, as well as an intermediate behaviour of the natural competitor and of our biocontrol agent. This protocol, applicable to different fungal phenotypical studies at both isolate and community level, allows a full exploitation of data obtained by the PM system and provides important information about the nutritional pattern of a single isolate compared to those of other fungi, a key factor to be exploited in biocontrol strategies. Abstract : Analysis of fungal phenotypes based on nutrients utilization: (a) exploratory clustering growth curves into groups (characterization); (b) confirmatory comparison and ordering isolates within substrates (assessment).